Prenatal dietary diversity may influence underweight in infants in a Ugandan birth‐cohort - Isabel Madzorera; Shibani Ghosh; Molin Wang; Wafaie Fawzi; Sheila Isanaka; Ellen Hertzmark; Grace Namirembe; Bernard Bashaasha; Edgar Agaba; Florence Turyashemererwa; Patrick Webb; Christopher Duggan (Wiley, 2021)
Abstract Growth faltering in early childhood is prevalent in many low resource countries. Poor maternal dietary diversity during pregnancy has been linked with increased risk of fetal growth failure and adverse birth outcomes but may also influence subsequent infant growth. Our aim is to assess the role of prenatal maternal dietary diversity in infant growth in rural Uganda. Data from 3291 women and infant pairs enrolled in a birth cohort from 2014 to 2016 were analysed (NCT04233944). Maternal diets were assessed using dietary recall in the second or third trimesters of pregnancy. Maternal dietary diversity scores (DDS) were calculated using the FAO Minimum Dietary Diversity for Women (MDD‐W). Cox regression models were used to evaluate associations of the DDS with the incidence of underweight, stunting and wasting in infants from 3 to 12 months, adjusting for confounding factors. The median DDS for women was low, at 3.0 (interquartile range 3.0-4.0), relative to the threshold of consuming five or more food groups daily. Infants of women in highest quartile of DDS (diverse diets) were less likely to be underweight (adjusted hazard ratio: 0.70, 95% confidence interval: 0.61, 0.80) compared with infants of women in Quartile 1 (p for trend <0.001) in models controlling for maternal factors. There was no significant association between DDS and stunting or wasting. Our findings suggest a relationship between higher maternal dietary diversity and lower risk of underweight in infancy. These findings suggest that programmes to improve infant growth could additionally consider strengthening prenatal dietary diversity to improve child outcomes globally.